Viva tutorials for surgeons in training (Greenwhich Medical Media, 2004)
This book is designed specifically for candidates preparing for the MRCS Viva examination. The format of the exam has been used in the book's structure, with over 1000 questions to illustrate the key points of over 200 topics. The book has been divided into 6 main chapters corresponding to a viva 'station' in the exam. Each chapter begins with a check-list of the main topics and themes covered by the exam, and information is then subdivided logically within the chapter itself. Key 'pass-or-fail' concepts are covered, and in some cases, topics are covered in more detail than will be asked in the exam, so the candidate can be confident that they will be fully prepared